Effects of Binders on Ma-khaen (Zanthoxylum limonella Alston) Bouillon Cube Qualities - มะโนแสน บุษบา -; กันทะขู้ จิรรัชต์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
Ma-Khaen (Zanthoxylum limonella Alston) is a local plant that found in Northern Thailand. It is a spice that has been used for enhancing the favor of local food. The aim of this research was optimized binder agent for seasoning development from Ma-Khaen. Three kinds of binders: tapioca starch, corn starch and wheat flour were studied in comparison with control group (No Binder). The product dimension was 2.5 x 3.0 x 1.0 centimeter, each cubes net weight was 10 grams. The average of water activity was 0.58, the solubility test at 80 oC of water temperature, wheat flour products were the fastest dissolving agent (8 minutes) followed by corn starch and tapioca starch. The sensory perceptions on color, scent, taste overall of each seasoning of Ma-khaen with tapioca starch, corn starch and control sample were accepted moderately tolerant binder, whereas, wheat-based products were less acceptation. The corn starch which more accepted moderately and solubility was the most suitable binder for bouillon cube products from Ma-Khaen.